2018
DOI: 10.1111/cei.13229
|View full text |Cite
|
Sign up to set email alerts
|

Anti-β2-glycoprotein I antibody with DNA binding activity enters living monocytes via cell surface DNA and induces tissue factor expression

Abstract: SummaryAutoantibodies characteristic for anti‐phospholipid syndrome (APS) and systemic lupus erythematosus (SLE) are anti‐β2‐glycoprotein I (β2GPI) antibodies and anti‐DNA antibodies, respectively, and almost half of APS cases occur in SLE. Anti‐β2GPI antibodies are recognized to play a pivotal role in inducing a prothrombotic state, but the precise mechanism has not been fully elucidated. In a widely accepted view, binding of anti‐β2GPI antibodies to cell surface β2GPI in monocytes and endothelial cells trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…As we have observed previously, anti-dsDNA antibody 2C10 enters live monocytes and the monocytic cell line THP-1 [16]. To confirm if the current batch of 2C10 actually enters live cells, we tested the effect of fixation and permeabilization (F/P) of THP-1 cells.…”
Section: Dna Enhances the Internalization Of Monoclonal Anti-dsdna Anmentioning
confidence: 93%
“…As we have observed previously, anti-dsDNA antibody 2C10 enters live monocytes and the monocytic cell line THP-1 [16]. To confirm if the current batch of 2C10 actually enters live cells, we tested the effect of fixation and permeabilization (F/P) of THP-1 cells.…”
Section: Dna Enhances the Internalization Of Monoclonal Anti-dsdna Anmentioning
confidence: 93%
“…Previously, based on the results of direct binding ELISA, we had reported that the monoclonal antibody WB-6 purified using a Protein-G column binds to both DNA and CL-b 2 GPI [16]. Although this was reproducible, we were not fully confident of the reactivity because one partner was nucleic acid and the other protein; do they share a common structure?…”
Section: Highly Purified Wb-6 Binds To Both Dna and Cl-b 2 Gpimentioning
confidence: 95%
“…WB-6 enters THP-1 cells, monocytes and endothelial cells [16]. In the present study, we investigated the kinetics of this phenomenon using PBMCs from healthy volunteers comparing WB-6 with other monoclonal anti-DNA antibodies.…”
Section: Kinetic Properties Of Anti-dna Antibody Internalizationmentioning
confidence: 96%
See 2 more Smart Citations